Development of a laboratory practice for physics introductory courses using a rubric for evaluation by competences. (August 2019) - Arribas, Enrique; Ramirez-Vazquez, Raquel; Escobar, Isabel; Gonzalez-Rubio, Jesus; Belendez, Augusto; Barrera, Josefina
Abstract: Competence-based education is oriented towards an evaluation model linked to student training, in order to foster the development of abilities to identify, project, solve problems and make decisions. In this context, the rubrics allow obtaining evidence of the acquisition of competences and application of knowledge outside the classroom. In this work, we present a proposal for the development of a Physics laboratory practice with the use of a rubric for the evaluation by competences in the university field. We want to introduce new assessment methods and identify opportunities to develop skills and evaluate learning through indicators of progress.